Flood Overflow Identification in Parit Indah Using Hec-Ras Model - Alkahfi Tarif, Eqiu; Malik, Yogi Septian; Ardeline, Mela (Journal of Engineering Science and Technology Management, 2025)
Flooding is an annual problem and has a major impact on the condition of society both economically, socially and environmentally. Flooding generally occurs due to overflowing rivers or the inability of rivers to accommodate excess river water due to high rainfall. The purpose of the study was to see how flood overflow in Parit Indah is simulated into a model so that it can be visualized and planned for appropriate and efficient control or mitigation efforts. The results of the analysis with the HEC-RAS model with input data of the maximum value of rainfall intensity in the last 10 years and the planned discharge of 2, 4, 6, 8 and 10 years, the results of the model exceeded the volume of the drainage channel and caused flood overflow around the beautiful ditch when the maximum rainfall intensity occurred